Reproductive performance of Murrah crossed buffalo at Buffalo Breeding Centre, Telupid, Sabah - Ahamad Suhaimi, Ahmad Zulhizri; Saad, Mohd Zamri (2012)
This study was conducted to determine the reproductive performance and the relationship between the rainfall pattern and the calf mortality of Murrah crossed buffalo managed in extensive farming system in Buffalo Breeding Centre Telupid Sabah. Retrospective data (2004-2011) of calving rate, pregnancy rate and calving interval were collected and analyzed using Microsoft Excel and SPSS software 16.0. Calf births and mortality data and the rainfall records from 2009 to 2011 were also collected and analyzed. The results showed that the mean calving rate was 25%; mean pregnancy rate was 43.6% and mean calving interval was 25.36 months. There was no significant difference detected between rainfall pattern and calf mortality although they were positively correlated (r > 0). Calf birth and mortality were highest during the rainy months each year (October to January). The buffalo also had a longer average calving interval of 740 days and this could be contributed by the nutrition provided and environmental condition of the farm (rainfall, ambient temperature) as well as the fertility of the bull and the dam themselves. It can be concluded that the buffalos in the extensive farm were not performing to their highest reproductive performance when compared with other reports on buffalo reproduction managed extensively.